2021
DOI: 10.7759/cureus.18034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Moderate Hypofractionated Volumetric-Modulated Arc Therapy Plans With and Without Flattening Filter for Localized Prostate Cancer

Abstract: Background/Aim The aim of this study was to compare volumetric-modulated arc therapy (VMAT) radiation plans between conventional VMAT with flattening filter (cFF-VMAT) and flattening filter-free VMAT (FFF-VMAT) for localized prostate cancer. Materials and methods Ten patients with localized prostate cancer who underwent cFF-VMAT at Yokosuka General Hospital Uwamachi, Yokosuka, Japan, from July 2020 to October 2020 were enrolled. Dose-volume histogram (DVH) parameters of the tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…on moderately hypofractionated VMAT with FFF beams for localized prostate cancer found no significant differences in DVH parameters for the target volume and in all parameters for the bladder and rectum. 16 Furthermore, IMRT with a FFF beam can achieve dosimetrically and clinically acceptable plans, as reported by Tamilarasu et al 14 In a similar study, Kumar et al performed a feasibility study on RapidArc plans using FFF beam, which yielded similar target coverage and a significant increase in the target mean dose for cervical cancer. 15 Zhang et al dosimetrically evaluated patients with cervical cancer after hysterectomy and found similar targets and OAR sparing using VMAT with FFF beams.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…on moderately hypofractionated VMAT with FFF beams for localized prostate cancer found no significant differences in DVH parameters for the target volume and in all parameters for the bladder and rectum. 16 Furthermore, IMRT with a FFF beam can achieve dosimetrically and clinically acceptable plans, as reported by Tamilarasu et al 14 In a similar study, Kumar et al performed a feasibility study on RapidArc plans using FFF beam, which yielded similar target coverage and a significant increase in the target mean dose for cervical cancer. 15 Zhang et al dosimetrically evaluated patients with cervical cancer after hysterectomy and found similar targets and OAR sparing using VMAT with FFF beams.…”
Section: Discussionmentioning
confidence: 68%
“…A recent study by Takakusagi et al. on moderately hypofractionated VMAT with FFF beams for localized prostate cancer found no significant differences in DVH parameters for the target volume and in all parameters for the bladder and rectum 16 . Furthermore, IMRT with a FFF beam can achieve dosimetrically and clinically acceptable plans, as reported by Tamilarasu et al 14 .…”
Section: Discussionmentioning
confidence: 74%